2004
DOI: 10.1051/0004-6361:20040439
|View full text |Cite
|
Sign up to set email alerts
|

The WEBT campaigns on BL Lacertae

Abstract: Abstract. The Whole Earth Blazar Telescope (WEBT) collaboration has collected a large amount of optical and radio data on BL Lacertae in the last years, which, when added to literature data, allow to construct well-sampled light curves of the source from 1968 to the end of 2003. These optical and radio data are here analysed with three statistical methods designed for unevenly-sampled data trains in order to search for possible periodicities. While the main radio outbursts repeat every ∼8 years, with a possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 26 publications
9
70
0
1
Order By: Relevance
“…When the variable component dominates we get a chromatic behaviours. Villata et al (2004a) confirmed that the optical variations on short timescales can be interpreted due to strongly chromatic component while the longer timescale component as mildly chromatic component. The BWB trend could be explained by one component synchrotron model which tells that more intense the energy release, the higher the particular frequency (Fiorucci, Ciprini, & Tostiet al 2004) or due to the Doppler factor variations in a spectrum deviating from power law.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…When the variable component dominates we get a chromatic behaviours. Villata et al (2004a) confirmed that the optical variations on short timescales can be interpreted due to strongly chromatic component while the longer timescale component as mildly chromatic component. The BWB trend could be explained by one component synchrotron model which tells that more intense the energy release, the higher the particular frequency (Fiorucci, Ciprini, & Tostiet al 2004) or due to the Doppler factor variations in a spectrum deviating from power law.…”
Section: Discussionsupporting
confidence: 57%
“…Authors also detected hints of bluer-whenbrighter (BWB) trend but any relation between spectral and flux changes were absent. Later, Villata et al (2002Villata et al ( , 2004a confirmed the presence of BWB trend in short isolated outburst but not on long timescales for BL Lacertae, indicating two different components are operating. Heidt & Wagner (1996) found 80% of complete BL Lacerate objects to show IDV confirming it to be their intrinsic nature.…”
Section: Introductionmentioning
confidence: 92%
“…The correlation between optical and radio flux variations in BL Lacertae has been the subject of several studies, and most of them found a correlation with a long time delay (a few months) of the radio after the optical flux changes (see e.g. Hufnagel & Bregman 1992;Tornikoski et al 1994b;Clements et al 1995;Villata et al 2004a;Bach et al 2006;Villata et al 2009b). However, simultaneous variations have already been found (Tornikoski et al 1994a).…”
Section: Optical and Near-infraredmentioning
confidence: 99%
“…1 http://www.oato.inaf.it/blazars/webt/ results have been published by Villata et al (2002), Ravasio et al (2002), Böttcher et al (2003), Villata et al (2004b), Villata et al (2004a), Bach et al (2006), Papadakis et al (2007), Villata et al (2009b), Larionov et al (2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the radio band, it is a kpc-scale core halo and has a VLBI core jet to the south. The radio emission varies at higher frequencies, leading the lower-frequency emissions by several days to a few months (Villata et al 2004), and the optical variations lead the 15 GHz radio emissions by ∼100 days (Bach et al 2006). …”
Section: B0925 + 504 2fgl J09295 + 5009 (Isp Bl)mentioning
confidence: 99%